Quality of care, resource use and patient outcome by use of emergency response team compared with standard care for critically ill medical patients in the emergency department: a retrospective single-centre cohort study from Norway - Stig Tore Bogstrand; Stine Engebretsen; Rune Rimstad (BMJ Open)
Objective The study aimed to investigate quality of care, resource use and patient outcome in management by an emergency response team versus standard care for critically ill medical patients in the emergency department (ED). The emergency response team was multidisciplinary and had eight members, with a registrar in internal medicine as team leader.Design Register-based retrospective cohort study.Setting Tertiary hospital in Norway.Participants The study included 1120 patients with National Early Warning Score 2 (NEWS2) 5–10 points from 2015 and 2016. Patients missing ≥3 NEWS2 part scores, <18 years and with orders ‘Not for ICU’ or ‘Not for resuscitation’ were excluded.Outcome measures Quality of care: pain assessment documented, analgesics given within 20 min, complete set of vital signs documented and antibiotics within 60 min if sepsis. Resource use: >3 diagnostic interventions, critical care in the ED and ED length of stay (LOS) <180 min. Patient outcome: intensive care unit (ICU) admission, ICU LOS <66 hours, hospital LOS <194 hours and mortality.Results The median age was 66 years, 53.5% were male, 44.3% were admitted to the ICU and the mortality rate was 10.6%. Altogether 691 patients received team management and 429 standard care. Team management had a positive association with ‘complete set of vital signs documented’ (OR 1.720, CI 1.254 to 2.360), ‘analgesics given within 20 minutes’ (OR 3.268, CI 1.375 to 7.767) and ‘antibiotics within 60 minutes if sepsis’ (OR 7.880, CI 3.322 to 18.691), but a negative association with ‘ pain assessment documented’ (OR 0.068, CI 0.037 to 0.128). Team management was also associated with ‘critical care in the ED’ (OR 9.900, CI 7.127 to 13.751), ‘ED LOS <180 min’ (OR 2.944, CI 2.070 to 4.187), ‘ICU admission’ (OR 2.763, CI 1.962 to 3.891) and ‘mortality’ (OR 1.882, CI 1.142 to 3.102).Conclusions Team management showed positive results for quality of care and resource use. The results for later outcomes such as mortality, ICU LOS and hospital LOS were more ambiguous.